Simulation of pellet ELM triggering in low-collisionality, ITER-like discharges. (18th November 2021) - Wingen, A.; Lyons, B.C.; Wilcox, R.S.; Baylor, L.R.; Ferraro, N.M.; Jardin, S.C.; Shiraki, D.
Abstract: 3D nonlinear, as well as 2D linear M3D-C1 simulations are used to model ELM triggering by small pellets in DIII-D discharges in the ITER relevant, peeling-limited pedestal stability regime. A critical pellet size threshold is found in both experiment and modeling depending on pedestal conditions, pellet velocity and injection direction. Using radial injection at the outboard midplane, the threshold is determined by M3D-C1 for multiple time slices of a DIII-D low-collisionality discharge that has pellet ELM triggering. Experimental observations show that a larger pellet size than the standard 1.3 mm diameter is necessary for ELM triggering; 1.8 mm pellets triggered several ELMs in cases where a smaller pellet failed. The M3D-C1 simulations are in good agreement with these observations. While the 2D linear simulations give insight into the change of growth rates for various toroidal modes with pellet size, the 3D nonlinear simulations apply a pellet ablation model that mimics the actual injection with good match to the experiment. The 3D nonlinear simulation confirms the pellet ELM triggering for a pellet size larger than the threshold found by the linear simulations.